A Qualitative Study of Social Media Marketing in Ireland: The Facilitating Role of Higher Education - Simon Stephens; Christopher McLaughlin (ÜNİVERSİTEPARK Limited, 2020)
In this paper we present a qualitative study of social media marketing by small business owners in Ireland. We present data from interviews with six owner/managers, six employees, and six experts. Exploring the three perspectives simultaneously facilitates a three-way narrative. We apply narrative structuring as proposed by Kvale (2006) in order to provide insight into the understanding, practices, motivations, behavior, and activities of small businesses as they relate to marketing; specifically, social media-based marketing. The delivery of skills to small businesses create challenges for higher education in terms of the design of curriculum, pedagogy and accreditation. A significant finding of this study is the influence that the attitudes, knowledge and capacity of the owners have on their propensity to engage with social media marketing. There is a role for higher education in bridging this gap. However, this is not just in the delivering of traditional skills, but working as facilitators and developing student, graduate and employee advocates through a comprehensive provision of experiential and work-based learning initiatives. This paper presents novel insights and improves our understanding of the role of higher education in supporting the training needs of small businesses. In our conclusion we present a series of recommendations on the design of customized training programs for small businesses.